2023
DOI: 10.1159/000529255
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Predictors of Longitudinal Cognitive Outcomes in Persons with Mild Cognitive Impairment

Abstract: <b><i>Introduction:</i></b> The study aimed to explore longitudinal cognitive outcomes and to ascertain predictors of conversion to dementia in a hospital-based mild cognitive impairment (MCI) cohort classified according to the neuropsychological phenotype at baseline. <b><i>Materials and Methods:</i></b> Subjects aged &gt;55 years who had a clinical diagnosis of MCI at initial visit between 2010 and 2018, with at least one formal neuropsychological assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
1
1
Order By: Relevance
“…First, the transition rate to dementia is as follows: among 1,375 older adults diagnosed with MCI through an early dementia screening in the community, 83.0% (1,141 people) remained with MCI for 3 years, and 17.0% (234 people) transitioned to dementia. A longitudinal study of cognitive changes over 8 years in older adults with MCI aged 55 years or older enrolled in a dementia clinic in Switzerland [15] reported that 22.2% (n = 21) of 95 individuals transitioned to dementia, which is approximately 5.0% higher than this current study. In South Korea, a study analyzing cognitive changes and influencing factors over a 2-year period in older adults with MCI aged 65 years and older using data from the 6th and 7th KLoSA [8] reported that 21.0% (n = 162) of the 773 subjects transitioned to dementia, which was 4.0% higher than this current study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…First, the transition rate to dementia is as follows: among 1,375 older adults diagnosed with MCI through an early dementia screening in the community, 83.0% (1,141 people) remained with MCI for 3 years, and 17.0% (234 people) transitioned to dementia. A longitudinal study of cognitive changes over 8 years in older adults with MCI aged 55 years or older enrolled in a dementia clinic in Switzerland [15] reported that 22.2% (n = 21) of 95 individuals transitioned to dementia, which is approximately 5.0% higher than this current study. In South Korea, a study analyzing cognitive changes and influencing factors over a 2-year period in older adults with MCI aged 65 years and older using data from the 6th and 7th KLoSA [8] reported that 21.0% (n = 162) of the 773 subjects transitioned to dementia, which was 4.0% higher than this current study.…”
Section: Discussioncontrasting
confidence: 74%
“…The differences or similarities with our results may be due to the following reasons. First, the time of change in cognitive function in previous studies varied from 1 year [16] to 8 years [15], whereas in this study, dementia transition was tracked for 3 years, which may have affected the transition rate. Second, the diagnostic process of MCI in this study was based on the MMSE-DS; if the sex-, age-, and education-adjusted z-score was less than -1.5 standard deviations from the mean score, the patient was classified as cognitively impaired and was referred to the detailed examination.…”
Section: Discussionmentioning
confidence: 93%